Answer:
The composition of f and g is given by
[tex]f(g(x))=4x(4x+6)+9[/tex]
Step-by-step explanation:
Given function f is defined by [tex]f(x)=x^{2}[/tex] and the
function g is defined by [tex]g(x)=4x+3[/tex]
Now to find the composition of f and g:
ie.,to find f(g(x)):
we know that [tex](f \circ g)x=f(g(x))[/tex]
[tex]f(g(x))=f(4x+3)[/tex]
[tex]f(g(x))=(4x+3)^{2}[/tex]
[tex]f(g(x))=(4x)^{2}+2(4x)(3)+(3)^{2}[/tex]
[tex]f(g(x))=16x^{2}+24x+9[/tex]
[tex]f(g(x))=4x(4x+6)+9[/tex]
Therefore [tex]f(g(x))=4x(4x+6)+9[/tex]
Therefore the composition of f and g is [tex]f(g(x))=4x(4x+6)+9[/tex]